STUDY OF TISSUE INFLAMMATORY RESPONSE TO IMPLANTATION OF A BIODEGRADABLE POLYMER COMPARED TO POLYPROPYLENE IN AN ANIMALS EXPERIMENT - Игорь Александрович Эйзенах; Максим Александрович Бакарев; Галина Анатольевна Лапий; Вадим Гельевич Мозес; Кира Борисовна Мозес (Медицина в Кузбассе)
The aim of research – to study qualitative and quantitative composition of inflammatory infiltration, formed around implanted biodegradable polymer in compare with polypropylene in experiment with animals.